Patrón de bandas en Aeromonas y Plesiomonas shigelloides aisladas en productos agrícolas y aguas de riego - Carla Paola, Melendrez Toaza (2021)
Abstract This research work was carried out through a bibliographic review, the objective proposed was to analyze the study of the pattern of genetic bands obtained by the Polymerase Chain Reaction in Aeromonas and Plesiomonas shigelloides isolated in agricultural products and irrigation waters, which allowed intraspecific genotypic differentiation. Considering that gastrointestinal infections are diseases that affect humans very frequently, it is important to identify these bacteria by means of primers that allow the amplification of gene fragments for their recognition. Therefore, the contribution and production of knowledge about new innovative methodologies is very relevant since it is a starting point for future research in microbiology and molecular biology; with regard to products for human consumption. This study was based on a retrospective documentary research design, 103 scientific articles were found in the review process, through the inclusion and exclusion criteria, a total of 25 articles were selected, which are in the Spanish and English languages, they were located in Scopus, SciELO, Pubmed, Npunto, Unam; they were gathered from 10 years ago. After the research was concluded, it was followed by the analysis and discussion of several authors on the subject, the proposed objective was achieved. It is recommended to carry out field and experimental research related to the subject because in our country there are few bibliographic references on it to reduce gastrointestinal diseases caused by Aeromonas and Plesiomonas shigelloides. Keywords: Aeromonas sp, Plesiomonas shigelloides, random amplification of polymorphic DNA, polymerase chain reaction, gastrointestinal infections. Reviewed by: Mgs. Geovanny Armas Pesántez ENGLISH PROFESSOR C.C. 0602773301